Applying the anisotropy of magnetic susceptibility technique to the study of the tectonic evolution of the West Spitsbergen Fold-and-Thrust Belt - Katarzyna Dudzisz; Rafał Szaniawski; Krzysztof Michalski; Geoffrey Manby (Polar Research, 2016)
We demonstrate the use of the anisotropy of magnetic susceptibility (AMS) method to determine the orientation of the principal tectonic strain directions developed during the formation of the West Spitsbergen Fold-and-Thrust Belt (WSFTB). The AMS measurements and extensive rock-magnetic studies of the Lower Triassic rocks reported here were focused on the recognition of the magnetic fabric, the identification of ferromagnetic minerals and an estimation of the influence of ferro- and paramagnetic minerals on magnetic susceptibility. At most sites, the paramagnetic minerals controlled the magnetic susceptibility, and at only one site the impact of ferromagnetic minerals was higher. The AMS technique documented the presence of different types of magnetic fabrics within the sampled sites. At two sites, a normal (Kmin perpendicular to the bedding) magnetic fabric of sedimentary origin was detected. This was associated with a good clustering of the maximum AMS axes imposed by tectonic strain. The Kmax magnetic lineation directions obtained here parallel the general NNW–SSE trend of the WSFTB fold axial traces and thrust fronts. The two other investigated sites possessed mixed and inverted fabrics, the latter of which appear to reflect the presence of iron-bearing carbonates.